The Australian Child Maltreatment Study (ACMS): Protocol for a national survey of the prevalence of child abuse and neglect, associated mental disorders and physical health problems, and burden of disease - Mathews, B.; Pacella, R.; Dunne, M.; Scott, J.; Finkelhor, D.; Meinck, F.; Higgins, D.J.; Erskine, H.; Thomas, H.J.; Haslam, D.; Tran, N.; Le, H.; et al. (2021)
Introduction: Child maltreatment (physical abuse, sexual abuse, emotional abuse, neglect and exposure to domestic violence) is widely understood to be associated with multiple mental health disorders, physical health problems and health risk behaviours throughout life. However, Australia lacks fundamental evidence about the prevalence and characteristics of child maltreatment, its associations with mental disorders and physical health, and the associated burden of disease. These evidence gaps impede the development of public health strategies to better prevent and respond to child maltreatment. The aims of this research are to generate the first comprehensive population-based national data on the prevalence of child maltreatment in Australia, identify associations with mental disorders and physical health conditions and other adverse consequences, estimate attributable burden of disease and indicate targeted areas for future optimal public health prevention strategies.